Stock market prices and the market for corporate control - Armour, J; Cheffins, B (University of Illinois, 2016)
The manner in which hostile takeovers have historically been executed has just begun to receive serious academic attention. Similarly, while the literature on the accuracy and determinants of share prices is voluminous, there has been little systematic historical analysis of when and how modern standards of share price efficiency took shape. This Article addresses both subjects in depth to ascertain the extent to which developments in the market for corporate control may have been associated with, or facilitated by, developments in stock market efficiency. We identify potential linkages between hostile control transactions and stock market pricing and explore these linkages empirically with a new hand-collected dataset of control contests occurring between 1900 and 1965. We show that, while the evolution of acquiror tactics in control contests was plausibly linked in some circumstances to changes affecting the manner in which shares were priced, other factors have to be taken into account to explain how the market for corporate control developed over this period.